Efecto de los metabolitos de las raíces de Avena sativa, Medicago sativa, Brachiaria decumbens y Brassica juncea en la degradación de PCBs. (2017)
ABSTRACT: This work evaluated the effect of compounds releases during the root turnover of Avena sativa, Medicago sativa, Brachiaria decumbens and Brassica juncea on degradation of 6 Polychlorinated biphenyls congeners, in a soil polluted with Aroclor 1260. The tests were conducted in microcosm with 20 g of soil to which were added crushed roots of plants previously grown in soil contaminated with PCBs. Microcosms with biphenyl, salicylic acid, and without additions were used as controls. Microcosms were incubated for 45 days under controlled conditions. After incubation time, concentration of PCBs 44, PCB66, PCB118, PCB138, PCB153, PCB180 and PCB170 was determined. BphA1 gene concentration and hydrolysis of fluorescein were also evaluated. Root extracts of plants were analyzed in order to identify some secondary metabolites. In the microcosm with Brassica juncea and biphenyl concentration decreasing of PCBs 66, 118, and 138 was observed. The higher concentration of BphA1 gene and fluorescein was also observed in Brassica juncea and biphenyl microcosms. The analysis of root extracts allowed identifying different secondary metabolites associated with the roots plant, especially in Brassica juncea root extracts. The results allowed testing the effect of the compounds released by the roots of certain plants in the soil microbial populations capable of degrading PCBs.